2016
DOI: 10.1111/iej.12627
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic mechanisms of human dental pulp and their relationship with substance P expression in response to occlusal trauma

Abstract: Caviedes-Bucheli J, Gomez-Sosa JF, Azuero-Holguin MM, Ormeño-Gomez M, Pinto-Pascual V, Munoz HR.Angiogenic mechanisms of human dental pulp and their relationship with substance P expression in response to occlusal trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
47
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 63 publications
3
47
0
2
Order By: Relevance
“…Mechanisms including endogenous release of substance P, which activate the survived root odontoblasts and increase their biosynthetic activity, have been suggested (Caviedes‐Bucheli et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Mechanisms including endogenous release of substance P, which activate the survived root odontoblasts and increase their biosynthetic activity, have been suggested (Caviedes‐Bucheli et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Caviedes‐Bucheli et al . () showed that angiogenesis in the amputated dental pulp comprises two processes, either by modulating endothelial cell growth (direct mechanism) or by attracting cells with angiogenic potential to the injury site (indirect mechanism). Formation of new vessels after the breakage of the pre‐existing vasculature is regulated by a variety of signalling molecules, such as growth factors and endogenous pulp substances (Smith & Cooper ).…”
Section: Discussionmentioning
confidence: 99%
“…Dental pulp stem cells (DPSCs) play two important roles in pulp revascularization. First, they contribute to the angiogenic process by secreting proangiogenic factors, including platelet‐derived growth factor AB (PDGF) and vascular endothelial growth factor (VEGF), as a result of hypoxia or injury (Bronckaers et al , Caviedes‐Bucheli et al ). VEGF best induces angiogenesis or vasculogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…PRGF was used in the surgically prepared socket, because it is an autologous scaffold obtained by platelet activation and fibrinogen polymerization, and contains most of the growth factors and proteins involved in angiogenesis (Caviedes‐Bucheli et al ). Several studies have highlighted the anti‐inflammatory and anti‐bacterial properties of this preparation, as well as its capacity to promote key healing processes such as collagen production, cell differentiation and angiogenesis (Anitua et al ,b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation